(untitled) (Journal of the College of Education for Women, 2019)
Diversity of the aspects of analyzing a specific linguistic issue is considered to be afamiliar phenomenon in learning Arabic in which – at different levels- various linguisticaspects and phases – sometimes – are involved in a linguistic issue . In this paper , theproblematic issues during linguistic analysis are taken into an account. The Holy Quraninterpretation books include many Quranic expressions which have a lot of meaning describedby different interpreters , from them this paper has selected only one expression ( = كفاتاreceptacle ) from the verse "Have we not made the earth a receptacle " ( Al- Mursalat verse 25) , this paper believes that this expression is sufficient display the interpreters’ views andopinion which explain this expression in a variable unimaginable way . Understanding thisaspect emerges form the interpreter as he/she sees the context in which the meaning of anexpression appears . It is believed that any given text is determined by the interpreter’s cultureand instinct . Thus , meaning may vary , as viewed by an interpreter or a group of interpreters, and this shall consequently lead to diversity in interpretation . Understanding of meaning canbe differently comprehended due to different interpreters or different context. The aspectwhich tackle the semantic side of ( كفات ) are six . These aspects have been morphologically and syntactically analyzer so as to determine the aspect meant by the Holy Quran itself . Thiscan be realized by extending the views related to its semantic side taking into considerationthe measure ( فعال ) which is characterized by its semantic diversity in Arabic expression andtheir formation , i.e., (the sound /k/,/f/ and /t/) . Moreover , this paper shows the concisesemantic differences between ( كفات ) and its counterparts in the Holy Quran which havesecondary measurement which appear in the earth stretching verses such as (carpet ( , (بساطtractable ( ذلول ) , bed ( فراش ) , floor ( قرار ), and cradle ( (مھاد- م